2008
DOI: 10.2298/hel0848085v
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of sunflower (Helianthus annuus L.) to imazethapyr

Abstract: The response of RIMI [imazethapyr-tolerant (T)] sunflower (Helianthus annuus L.) hybrid and the local imazethapyr-sensitive hybrid "Zoltan" (S) was investigated under controlled conditions. Hybrids grown in pots were treated post-emergence with imazethapyr at the two pairs of leaves stage. Visual injury evaluation and vegetative parameters were recorded. ALS (acetolactate synthase) enzyme activity was estimated in vivo 24 h after imazethapyr application. Tolerance level was determined based on the resistance r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…This confirms previous studies that suggested that salt stress reduced the biomass of tomato [29], pea [30], Phaseolus [31] and rice [32]. The significant dropped in root and shoot development may be due to toxic effects of NaCl as well as unbalanced nutrient uptake by the seedlings [15].Hence, results found by [33] confirmed this explication.…”
Section: Discussionsupporting
confidence: 90%
“…This confirms previous studies that suggested that salt stress reduced the biomass of tomato [29], pea [30], Phaseolus [31] and rice [32]. The significant dropped in root and shoot development may be due to toxic effects of NaCl as well as unbalanced nutrient uptake by the seedlings [15].Hence, results found by [33] confirmed this explication.…”
Section: Discussionsupporting
confidence: 90%
“…White et al assessed in vivo AHAS activity on an imazethapyr-resistant sunflower biotype founded in Howard, South Dakota, that showed an I 50 of 200 mM (39-fold more resistant than the susceptible biotype) [30]. Other researchers found that in vivo AHAS inhibition by imazethapyr was 210 folds higher in resistant sunflower hybrid when compared to susceptible hybrid [31]. Previous research on imidazolinone resistant wild sunflower has shown similar results at the enzyme level.…”
Section: Resultsmentioning
confidence: 95%
“…The duration of competitive interactions determines the final losses in the growth and development of the plant, and therefore in the crop yield. Planting competitive cultivars at relatively high seeding rates, with controlled application of fertilizers (subsurface banded or point-injected nitrogen), could reduce the negative impacts of weeds on the crop and the amount of weed seeds in the seed bank [68,71]. Cultivars may vary in their competitiveness because weeds reduce the water and nutrient content in the soil profile, making this resource less available, leading the crops into a state of stress, slowing down their growth and development and finally reducing their yield [72].…”
Section: Crop Competitivenessmentioning
confidence: 99%